EDUKASI PENGARUH WEBSITE PELAYANAN KESEHATAN TERHADAP KESADARAN DAN KEPATUHAN BEROBAT DI DESA - Lidya Paramitha Moha; Defita Sari Lahasa; Maimuna Rauf (Journal of Hulonthalo Service Society (JHSS), 2024)
Effective health services do not only depend on the quality of health facilities, but also public awareness of actively seeking health information and treatment. The health service website is one of the innovations that has an influence on increasing public awareness and compliance in treatment. This Community Service aims to educate the public on the importance of using health service websites and their influence on awareness and compliance in treatment. This service activity was carried out in Talumelito Village, Gorontalo Regency. The method used is education and interactive discussions designed to provide an in-depth understanding of the use of health service websites. The results of the activity showed that there was an increase in public knowledge about health information and was more encouraged to use health services regularly.